2012
DOI: 10.4314/ahs.v12i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase C677T polymorphism and breast cancer risk in Moroccan women

Abstract: Background: Methylenetetrahydrofolate (MTHFR) enzyme plays an important role in folate metabolism which is involved in DNA methylation, repair, and synthesis. Objective: We investigated if the MTHFR C677T polymorphism modulates the risk of developing breast cancer in Moroccan women. Methods: Genotyping was performed by PCR-RFLP method on a sample of 96 patients with breast cancer and 117 controls. Results: A positive correlation was found between the MTHFR C677T polymorphism and progesterone receptors expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
3
13
1
1
Order By: Relevance
“…However, we observed no significant association of intake of folate, vitamin B6 and vitamin B12 with risk of breast cancer, and no significant interaction between MTHFR C677T polymorphism and folate intake on the risk of breast cancer. Recently, several studies have reported the association between MTHFR C677T and A1298C and MTR A2756G polymorphisms and risk of breast cancer, but the results of our study are consistent with those of previous studies (Cho et al, 2007;Larsson et al, 2007;Gao et al, 2009;Webb et al, 2011;de Cássia Carvalho Barbosa et al, 2012a, b;Lajin et al, 2012;Diakite et al, 2012). Therefore, we investigated the role of MTHFR C677T and A1298C and MTR A2756G polymorphisms in the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…However, we observed no significant association of intake of folate, vitamin B6 and vitamin B12 with risk of breast cancer, and no significant interaction between MTHFR C677T polymorphism and folate intake on the risk of breast cancer. Recently, several studies have reported the association between MTHFR C677T and A1298C and MTR A2756G polymorphisms and risk of breast cancer, but the results of our study are consistent with those of previous studies (Cho et al, 2007;Larsson et al, 2007;Gao et al, 2009;Webb et al, 2011;de Cássia Carvalho Barbosa et al, 2012a, b;Lajin et al, 2012;Diakite et al, 2012). Therefore, we investigated the role of MTHFR C677T and A1298C and MTR A2756G polymorphisms in the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…We found no association between MTHFR A1298C polymorphism and breast cancer risk. Our findings are consistent with previous studies on the association between variants of MTHFR gene and folate and risk of breast cancer (Gao et al, 2009;Alshatwi, 2010;Hosseini et al, 2011;de Cássia Carvalho et al, 2012;Diakite et al, 2012;Lajin et al, 2012;Wu et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Another study in a Moroccan population conducted by Diakite et al (2012) involving 96 women found an association between at least one polymorphic allele and breast cancer increased risk, contrary to our findings. In our study, we found no statistically significant differences between 677CT+TT and 677CT genotypes in both types of cancers studied.…”
Section: Discussioncontrasting
confidence: 57%
“…This polymorphism is associated with a reduction in the MTR enzyme, leading to elevated homocysteine level and DNA hypomethylation (Hosseini, 2013). Studies on polymorphisms and cancer risk presented controversial results due to several factors such as a measurement sample, ethnicity and population studied, hormones, and environmental factors such as folate intake (Diakite et al, 2012;Gong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation